Religion, federalism, and the struggle for public life : cases from Germany, India, and America - Everett, William Johnson (Oxford University Press, 1997)
Through a comparative study of India, Germany and the USA, this text examines the roles of religious traditions in the development of modern federal republicanism. It argues that a better comparative grasp of political and religious dynamics is essential to our understanding of the establishment, sustenance, and development of federal republican governance in both Western and non-Western cultures.